The effect of prolonged incubation and temperature on oocyte activator phospholipase C-zeta activity of sperm - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2017)
Objective: Fertilization capacity of capacitated sperm decreases exponentially over time, but the reason is still under investigation. The aim of the study was to analyze the effect of prolonged incubation and temperature on sperm fertilization capacity with motility and staining parameters of phospholipase C-zeta (PLCZ), which is considered to be the oocyte activation factor. Materials and Methods: Density gradient washing was applied to semen of 11 infertile patients without severe oligoasthenospermia out of 16 patients. The samples were divided and cultured either at room temperature or at 37 degrees C for 3 days. The spermatozoons were evaluated for motility, PLCZ staining and intensity daily. Results: All parameters decreased both at room and body temperature with increased incubation time. There was a strong correlation between the change in motility and in the percentage of PLCZ stained sperms, but this correlation decreased with incubation time. Conclusion: Prolonged incubation results show the correlation between PLCZ staining parameters and motility. Routine use of PLCZ staining together with semen analysis, will be useful to predict fertilization capacity of the sperm especially for unexplained infertility and fertilization failure cases, and also can increase the success of assisted reproductive technologies (ART) cycles.
Keywords: Temperature; Phospholipase C-zeta; Fertilization capacity; Sperm; Oocyte activaton; Prolonged incubation; PLC-ZETA; FERTILIZATION RATES; IN-VIVO; SPERMATOZOA; TRANSPORT; SURVIVAL; MOTILITY; VIABILITY; QUALITY; SEMEN